Klasifikasi Varietas Unggul Padi menggunakan Algoritme C4.5 - Arinda Rachman; Muhammad Tanzil Furqon; Fatwa Ramdani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Superior varieties are important supporting component in increasing national rice production. Each type of superior variety has different characteristics. Farmers need knowledge to be able to choose the type of rice they want while keeping rice production stable. To overcome the problem in determining rice seeds, one solution is to use data mining classification. The classification are using the decision tree method, with the C4.5 algorithm. C4.5 algorithm is an algorithm that builds decision trees from data with recursive patterns. C4.5 goes to each node of the decision tree, then selects the optimal branch until no more branches are generated. the algorithm can produce a classification of superior rice varieties needed to be planted in the fields. This research has input data in the form of flag leaves, grain shape, grain color, rice texture and texture. The input data is then processed by the C4.5 algorithm to produce outcomes that determine superior varieties of rice. The results of this study indicate that the classification performance of superior rice varieties is more influenced by the grain form attributes compared to other attributes. Meanwhile, the accuracy of the highest C4.5 algorithm in the k-fold 1 calculation was 28.571%. Meanwhile, k-fold 2 was 17.857%, k-fold 3 was 10.344% and k-fold 4 was 10.714%.